Data mining algorithms - Chattamvelli, Rajan (Alpha Science International, 2011)
Suitable for scientists, senior undergraduate and graduate students in applied sciences, this book can be useful to sharpen their skills, to improve their general knowledge, and to explore the computational aspects of complex models and algorithms presented. It provides reader with unprecedented insights into the working of various algorithms